Implementation of Behavioristic Theory in Forming Students' Disciplinary Character in PAI Learning at SDN 1 Taman Ayu - Halimatuzzahrah; Syamsul Arifin (Bulletin of Science Education, 2024)
Disciplinary character helps students to develop self-control, and helps students recognize wrong behavior and then correct it. A learning theory that prioritizes change in the form of changes in knowledge, skills or attitudes is Behavioristic learning theory. The aim of this research is to find out how behavioristic theory is implemented in forming students' disciplined character in PAI learning at SDN 1 Taman Ayu. This type of research is descriptive research with a qualitative approach, data collection techniques used in the form of observation, interviews and documentation. Data analysis techniques include data reduction, data presentation, drawing conclusions and verification. This research was conducted at SDN 1 Taman Ayu. Based on the research results, it was found that the application of behavioristic theory to PAI learning has been implemented well in accordance with the principles contained in behavioristic theory by increasing stimulus so that it can produce the desired response. In the application of behavioristic theory at SDN 1 Taman Ayu, the disciplined character of students that is formed includes: 1) students enter the class according to the specified time, 2) Students obey the class rules, in this case the rules are that the teacher does not start the learning process during class not yet clean, 3) Be orderly in following the learning process, 4) Maintain cleanliness and order in the classroom, 5) Complete teacher orders according to the time given, and 6). Collect assignments on time.